2017
DOI: 10.1016/j.jimonfin.2017.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Dutch disease, real effective exchange rate misalignments and their effect on GDP growth in EU

Abstract: In this article we study the impact of real effective exchange rate misalignments, based on determinants, including different types of foreign capital inflows, on GDP growth in the EU. This can provide a useful contribution to understanding the causal link between inflows, real effective exchange rate disequilibria and GDP growth during both the boom and the crisis period. For this analysis, we use a panel of 27 EU countries for the period 1994-2012, with annual frequency. We find that the core countries have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 59 publications
(72 reference statements)
1
21
1
Order By: Relevance
“…In line with this argument, Avdjiev, Binder, and Sousa () find that large foreign capital flows and a higher share of external lending is associated with a greater likelihood of credit booms. Capital flows that fuel the nontradable sectors of the economy would worsen both the internal and the external terms of trade and shift the current account into negative territory (Comunale, ; Dell'Ariccia et al, ).…”
Section: The Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this argument, Avdjiev, Binder, and Sousa () find that large foreign capital flows and a higher share of external lending is associated with a greater likelihood of credit booms. Capital flows that fuel the nontradable sectors of the economy would worsen both the internal and the external terms of trade and shift the current account into negative territory (Comunale, ; Dell'Ariccia et al, ).…”
Section: The Resultsmentioning
confidence: 99%
“…Lastly, we run the regressions adding a control for spillovers across member states, applying two different ways to account for this specific issue. First, we add either a weighted measure of GDP growth of the rest of the EU (Equation ), as in Comunale (), or the weighted average of the financial cycles of the rest of the EU (Equation ), as in Comunale (). In the latter, values are based on a principal component analysis from annual data in which we use output gaps, credit and domestic demand growths, and we take the first (common) principal component .…”
Section: The Resultsmentioning
confidence: 99%
“…Moreover, Aghion et al (2009) showed that real exchange rate volatility has a negative impact on productivity growth, while Vieira et al (2013) revealed that high real exchange rate volatility has a negative impact on economic growth, albeit the impact of low volatility is positive. However, Comunale (2017) noted that exchange rate volatility does not have any robust effect on GDP growth.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, and more commonly, atheoretical filtering techniques can be employed. 20 Starting with Clark and MacDonald's (1998) seminal study, the Hodrick-Prescott (HP) filter, for example, has been used by Nouira andSekkat (2012), Schröder (2013) and Comunale (2017). In this paper too the baseline equilibrium RER values are obtained on the basis of HP-filtered explanatory variables.…”
Section: Deriving Equilibrium Valuesmentioning
confidence: 99%